Desain Profil Perusahaan Imigrasi Polonia Medan dengan Menggunakan Animasi Motion Graphics - Suriati, Suriati; Tommy, Tommy; Dafitri, Haida (Universitas Harapan Medan, 2024)
Creating an animation for the Polonia Medan Immigration Company Profile Design Using Motion Graphics Animation is a design that aims to provide information about the Polonia Medan Immigration Office, so that it can be known by the wider public while making this animation a medium for finding out what the public doesn't know about the Polonia Medan Immigration Office . Multimedia is a combination of three elements, namely sound, images and text which can create dynamic and interactive presentations.